A simplified single transseptal puncture approach using high-density 3D voltage mapping for atrial fibrillation ablation: acute complications and long-term results - Silva Cunha, Pedro; Teixeira, Bárbara Lacerda; Laranjo, Sérgio; Portugal, Guilherme; Valente, Bruno; Delgado, Ana Sofia; Pereira, Mariana; Rocha, António Condeixa; Brás, Manuel; Cruz, Madalena Coutinho; Paulo, Margarida; Lousinha, Ana; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background An ablation catheter and a circular mapping catheter requiring a double transeptal puncture (TSP) for left atrial access have been conventionally used for atrial fibrillation (AF) ablation. Recently, different operators have combined a single transseptal puncture technique with 3D high-density mapping catheters for pulmonary vein isolation (PVI). Objective This study aims to compare two strategies, single vs. double TSP, regarding the duration of the procedure, radiation time, complication rates, and outcomes. Methods Retrospective analysis of a large cohort of consecutive patients that underwent first PVI with radiofrequency energy (RF), using a point-by-point strategy, with a 3D mapping system, either with single or double TSP, according to the operator's choice. Results 285 patients with a mean age of 59.5 ± 11.6 years (36.5% female, 67.7% paroxysmal AF) underwent a point-by-point catheter ablation with RF between July 2015 and March 2020. The mean CHA2DS2-VASc score was 1.7 ± 1.3. Single TSP was performed in 115 (40.3%) patients and double TSP in 170 (59.6%). The operator's experience (≥5 years of AF ablation procedures) was equally distributed among the two groups. The average procedure time (133 ± 31.7 min vs. 123 ± 35.5 min, for single and double TSP, respectively) did reach a statistical difference between both groups (p = 0.008), but there was a substantial advantage regarding fluoroscopy time (13 ± 6.3 min vs. 19 ± 9.1 min, for single and double TSP, respectively; p < 0.001). Acute major complications present similar rates in both groups (2.6% vs. 2.3%, p = 0.799). At the 2-year follow-up, both groups had a similar sinus rhythm maintenance rate (76.5% vs. 78.8%, p = 0.646). Conclusion A simplified single-TSP technique using high-density multi-electrode 3D mapping is a safe and highly successful option for AF ablation. This approach yields a substantial reduction in fluoroscopy time, with the potential to avoid acute complications, compared to a conventional double-TSP strategy.